115k views
5 votes
Simplify 10+4×4÷2×(5-1+3)​

User Rex Logan
by
5.8k points

2 Answers

3 votes

Answer:

The answer is 66.

Explanation:

Use order of operation.

Parenthesis goes first, so first you do the problem in parenthesis.

5-1+3=7

Next, combine the answer and the rest of the problem.

10+4*4/2*7.

I'm this problem, multiplication goes first, so to need to multiply 4 by 4.

4*4=16.

So now the problem should look like this:

10+16/2*7

Next, divide 16 by 2

16/2=8

That leaves you with 10+8*7.

Multiply 8 by 7.

8*7=56.

The last problem is 10+56.

10+56=66

Therefore, the answer is 66.

User Swinders
by
5.7k points
6 votes

Answer:

66

Explanation:

User Brash Equilibrium
by
5.5k points